Deep sea archaeological survey in the Black Sea – Robotic documentation of 2, 500 years of human seafaring. (October 2019) - Pacheco-Ruiz, Rodrigo; Adams, Jonathan; Pedrotti, Felix; Grant, Michael; Holmlund, Joakim; Bailey, Chris
Abstract: Between 2015 and 2017 the Black Sea Maritime Archaeology Project (Black Sea MAP) discovered and recorded 65 shipwreck sites dating from the 4th Century BC to the 19th Century AD in the Bulgarian Exclusive Economical Zone (EEZ). Using state-of-the-art remotely operated vehicles to survey the seabed, the team captured more than 250, 000 high-definition (HD) photographs; hundreds of hours of ultra high-definition (UHD) video together with acoustic bathymetric, laser, side-scan sonar and seismic data. The wrecks were located in depths from 40 to 2200 m – those shipwrecks in the deeper range presented extraordinary archaeological preservation due to the Black Sea's anoxic conditions. This paper will introduce the range of deep-sea optic and acoustic survey techniques to accurately record and create 3D and pseudo 4D models of the shipwrecks. It will focus on a Early 4th Century BC shipwreck demonstrating the project's survey strategy as well as adaptations developed in response to operational conditions; the implementation of deep sea robotics to generate georeferenced high-resolution photogrammetric models and the benefits this has as an on-site, as well as a post-cruise, interpretative tool. It demonstrates that in-theatre acquisition and processing of high-quality datasets is a working reality and has fundamental implications for management as well as the advantages that this brings to the archaeological research process: Firstly, in the creation of spatio-temporal models, i.e., 4D representations of a site pre and post archaeological excavation and secondly, in monitoring such wreck sites, and provides a viable non-intervention tool for the assessment of sites as part of a long-term management strategy. It also shows the value of well-funded collaboration between academia and industry and that deep water archaeology can and must be totally in accordance to the 2011 United Nations Educational, Scientific and Cultural Organization (UNESCO) convention.